Nanostructured zinc oxide: role of physico-chemical properties into the biological activity and potential cytotoxicity of the material - Harmaza, Yuliya M.; Tamashevski, Alexander V.; Slobozhanina, Ekaterina I. (Experimental Biology and Biotechnology, 2024)
Over the past two decades, nanotechnology has become interesting not only for science, but also for industry. Application of nanotechnological approaches has provided opportunities for obtaining various nanoparticles and new materials based on them with specific properties different from the properties of microanalogues. These new materials include nanostructured zinc oxide, which has found application into the biomedical sector, including bioimaging and targeted drug delivery. The production of particles in the nanoscale range has made it possible to increase the active surface area of this type of materials in the occupied volume, which has led to an improvement into their chemical, electrical, magnetic, structural and (or) morphological properties. However, depending on the entry type to the human body, nanoparticles can travel to various organs and tissues, where they can cause side effects. So, it is important in vitro to simulate the interaction in vivo between nanoparticles and cellular systems for toxicological studies. Moreover, in order to correlate any toxic reactions with the type of nanoparticles, it is necessary to find out the degree of their ability to adsorb on the cell surface and penetrate inside cell. It is known that the cytotoxicity of nanostructured zinc oxide can also significantly depend on its physico-chemical properties, in particular on the size and shape of the particles. For this reason, understanding the relationship between cytotoxicity and the physico-chemical properties of nanoparticles seems relevant for the objective assessment of possible risks associated with their exposure. Thus, the review provides a comprehensive overview of the main mechanisms of nanomaterials action on the human organism, the role of their physico-chemical properties into the biological activity, as well as the questions of potential cytotoxicity of nanostructured zinc oxide.
Keywords: nanostructured zinc oxide; physico-chemical properties; biodistribution of nanoparticles; biological activity of nanomaterials; cytotoxicity; reactive oxygen species; apoptosis